Disinfecting handheld electronic devices with UV-C in a healthcare setting - Suzan Cremers-Pijpers; Carsten van Rossum; Mirjam Dautzenberg; Heiman Wertheim; Alma Tostmann; Joost Hopman (Elsevier, 2021)
Summary: Handheld Electronic Devices (HEDs) play a central role in the hospital environment. However, they can be a vehicle for transmitting (pathogenic) microorganisms. We studied whether disinfection with UV-C light is successful in disinfecting three different HEDs in a clinical setting. Disinfection with UV-C light was performed with the UV-Smart® D25. We took a total of 800 samples on two departments and counted colony forming units. More than half of the baseline measurements were moderately (>10CFU) or highly (>50 CFU) contaminated. Post-disinfection the CFU was 0 in 87% of measurements. We conclude that the UV-Smart® D25 can be used to disinfect non-critical HEDs in clinical healthcare.